Can currency crises be prevented or better managed? - Teunissen, Jan Joost ed. (FONDAD The HagueNL, 1996)
Assesses the Mexican crisis of 1994. Addresses the issue of how future currency crises such as that in Mexico can be prevented or better managed. Looks at what currency crises tell us about the future of the international monetary system.